One-step SDS-assisted hydrothermal synthesis and photoelectrochemical study of Ag4V2O7 nanorods decorated with Ag nanoparticles. Issue 35 (21st September 2015) - Wang, Jinxiu; Chen, Jing; Yu, Yanke; Yu, Weijia; Meng, Xiaoran; Chen, Jinsheng; Li, Danzhen
<x xml:space="preserve">Abstract</x> Ag/Ag4V2O7 nanocomposites showing good photoelectrochemical response have been synthesized and the possible crystal growth process has been discussed preliminarily.